Diode Amplitude Modulation and Demodulation - Ayad, Arwa A.; Hashim, Khalil I.; Khazmi, Yousef O. (Libyan Journal of Science &Technology, 2025)
Diode amplitude modulation and demodulation have been investigated and the modulation index and modulation percentage were calculated. Of the several amplitude modulation methods, the diode modulation has been chosen to execute the amplitude modulation process because it was the first method used and it is the simplest method. A 50 Hz sine wave is used as a modulating signal to amplitude modulate a 1 kHz sine wave used as a carrier wave. During the modulation process, the amplitude of the modulating signal was kept constant at a value of 6 V while the amplitude of the carrier wave was given values between 6 V to 12 V increasing the value in steps of 1 V. The shapes of the modulation stages and of the demodulation processes were displayed on the oscilloscope screen using the simulation programmed named NI Multisim 14.2. The experiments were also carried out practically in the advanced electronics laboratory in the Physics department/Faculty of Science/University of Benghazi using real electronic equipment and parts. The recovered audio signal in the demodulation process was the same as that used as a modulating signal.